Preparation of nanoemulsions by phase inversion temperature (PIT) method - A. Jintapattanakit (2019)
© 2018, Mahidol University - Faculty of Pharmacy. Nowadays, there is an increasing interest in the utilization of nanoemulsions in many industries, such as pharmaceuticals, food and beverage, cosmetics and agrochemicals because of a number of potential advantages over conventional emulsions (i.e., increased bioavailability, enhanced long-term stability and high optical clarity) and microemulsions (i.e., relatively low amount of surfactant used). The productions of nanoemulsions are typically divided into high-energy and low-energy emulsification methods. High-energy methods involve the use of mechanical devices to break up particles into smaller sizes. In contrast, low-energy methods divert the intrinsic physicochemical properties of surfactants, co-surfactants and excipients in the formulation, leading to the generation of emulsion droplets in the nanometric range. Owing to the advantages of low-energy methods (i.e., low cost and ease of implementation), there is considerable interest in the productions of nanoemulsions using low-energy methods, namely spontaneous emulsification, phase inversion composition, and phase inversion temperature (PIT). Among these, the PIT method is the most widely used in industry and has evidenced the progress in the knowledge of the factors leading to nanoemulsions with minimum size and low polydispersity index. In this review, the principle of the PIT method is presented. The major factors influencing nanoemulsion formation using the PIT method and its applications to other lipid-based nanocarriers are reviewed.